Personal Problems of the Main Characters in M3gan Movie - Virda nur faidah (CV. Kalimasada Group Profesional, 2023)
One of the literary works is film, in which from the past until now there have been many different developments in it, and there are many interesting stories, genres, plots in a film. In this film, Literature requires conflict because it provides the fundamental building blocks for story development. Without conflict, nothing will happen. There are a few issues to know about the M3gan movie, an inexperienced Gemma becomes a mother to take care of her niece, so she creates this genius robot with extraordinary prowess that turns out to be very dangerous for her environment. In the research, the writer uses a qualitative approach because according to him analyzing the film M3gan can be done by describing the main characters using their own words because it does not need to be calculated so that messages between films can be directed properly and film viewers can understand the intent of the film and descriptive methods can be interpreted as a problem solving procedure that is investigated by describing the state of the subject or object in research can be in the form of people, institutions, communities and others at this time based on visible facts.Keywords : Literature, Movie, Problem